Intercultural Communicative Competence in ELT: Lecturers’ Perception and Practice - Umi Fitriyah; Ahmad Munir; pratiwi retnaningdyah (IJET (Indonesian Journal of English Teaching), 2019)
“One of its obvious results is the emergence of intercultural communication and English language has then become as a bridge for cross-cultural communication, thanks to its worldwide lingua franca. For these reasons, Intercultural Communication Competence (ICC) should be more concerned in English Language Teaching (ELT) tertiary contexts. This study aims to gain an indepth understanding on this issue by investigating English teachers' perceptions and practices on ICC in ELT . The study uses a mixed method, to find the perspective of the lecturers, the researcher use questionnaire and interview, while for the practice the reseracher use observation. The findings of the study reveal the positive attitudes of English lecturers on ICC in ELT, but certain challenges confronted by their implementations have been highlighted. As a result, some possible measures to enhance ICC engagement in ELT in this context are proposed.”